Comparable Serologic Responses to 2 Different Combinations of Inactivated Hepatitis A Virus Vaccines in HIV-Positive Patients During an Acute Hepatitis A Outbreak in Taiwan. (16th April 2018) - Lin, Kuan-Yin; Hsieh, Szu-Min; Sheng, Wang-Huei; Lo, Yi-Chun; Chuang, Yu-Chung; Cheng, Aristine; Pan, Sung-Ching; Chen, Guan-Jhou; Sun, Hsin-Yun; Hung, Chien-Ching; Chang, Shan-Chwen
Abstract: We evaluated the serologic responses to different 2-dose combinations of the inactivated hepatitis A virus (HAV) vaccines Havrix and Vaqta among human immunodeficiency virus–positive individuals during an acute hepatitis A outbreak in Taiwan. In this 16-month retrospective study, one group received 1 dose of Havrix followed by 1 dose of Vaqta, and another group received 2 doses of Vaqta. The Havrix-Vaqta and Vaqta-Vaqta groups achieved similar seroconversion rates at weeks 28–36 (82.3% and 80.9%, respectively; absolute difference, 1.3% [95% confidence interval CI, −6.3%–3.7%]) and week 48 (94.7% and 94.4%, respectively; absolute difference, 0.3% [95% CI, −2.6%–3.2%]), suggesting the interchangeability of different combinations of HAV vaccines. The significantly higher seroconversion rate after the first dose of Vaqta, compared with the dose of Havrix (53.0% vs 32.4%) may provide potential benefits in preventing HAV infection during the outbreak. Abstract : Among human immunodeficiency virus–positive recipients of 2-dose combinations of Havrix-Vaqta or Vaqta-Vaqta during an acute hepatitis A outbreak, the Vaqta-Vaqta group had better serologic responses after the first dose, whereas the groups had similar serologic responses after the second dose.